Tutor profile: Troie O.
Solve this equation using substitution: 2x - 9y = 14 x = -6y + 7
X = 7 and Y = 0. First, you would plug in the second equation into the first, making it 2(-6y + 7) - 9y = 14. We are able to do this because we can substitute the second equation for x. We then distribute by multiplying 2 by -6x and then by 7 separately; we then get -12x + 14. So far, the full equation is -12y + 14 - 9y = 14. We want to add like terms, so we are going to subtract 14 by 14 (getting zero) and we are going to subtract -12y by -9y, getting -21y. Now, we have -21y = 0; the answer will be y = 0 because anything divisible by 0 is 0. To find x, we are simply going to plug y into the second equation, x = -6y + 7. When we do this, we will get x = -6(0) + 7, leaving us with x = 7, because anything multiplied by 0 is also 0. Our final answers will be X = 7 and Y = 0.
Subject: World History
Who was the English king that had six wives and broke away from the Catholic church so he could divorce?
Find the Gerund in this sentence: He enjoys reading because it helps him to relax.
The gerund would be reading, because it is a noun made from a verb. Gerunds can be subjects, complements, or objects of a sentence.
needs and Troie will reply soon.